Determinación de TGP, FA, GGT y su relación con el tiempo de consumo de alcohol para desencadenar un posible daño hepático en los alcohólicos anónimos - Cárdenas Cando, Yudy Karely (2015)
The alteration of liver enzymes put in evidenced the liver damage caused by the excessive consumption of alcohol, it can cause three types of liver damage: the accumulation of fat (fatty liver), inflammation (alcoholic hepatitis) and the appearance of scarring (cirrhosis). Determined values of Transaminase Glutamo Pyruvic (TGP), Alkaline Phosphatase (FA), Gamma Glutamyl Transcriptase (GGT) and its relationship to the time of alcohol consumption to trigger a possible liver damage in Alcoholics Anonymous belonging to the Centre Municipal Social Support (CASMUL) in the Centre of Rehabilitation "Posada Solidarity". The study is of type quantitative, descriptive, cross section, where they worked with 61 patients who met the inclusion criteria. Increased values were obtained: TGP 56%, 52% FA and GGT 15%; and a decreased in GGT 1% value, as at the time of alcohol consumption, we find that: 1 to 19 years 66%; 20 to 39 29% and 40 to 50 years 5% of the total of 61 samples analyzed. The relationship between liver with alcohol consumption time, we find the following ranges from 1 to 19 years with increased values in the patients of TGP 22, FA 23 and GGT 3; 20 to 39 years with increased TGP 11, FA 6 and 5 GGT values; last 40 to 50 years with increased TGP 1, FA 2, and GGT 1 values; There is greater alterations in the liver tests in the range of 1 to 19 years, since the same takes a period of abstinence approximately 2 to 3 weeks, which influences the altered results; Similarly was the delivery of results to those responsible of the center of Rehabilitation. KEY WORDS: ALCOHOLISM, LIVER DAMAGE, LIVER ENZYMES.